Phosphorylated alpha‐synuclein in Iba1‐positive macrophages in the skin of patients with Parkinson's disease - Hideki Oizumi; Kenshi Yamasaki; Hiroyoshi Suzuki; Saki Ohshiro; Yuko Saito; Shigeo Murayama; Yoko Sugimura; Takafumi Hasegawa; Kohji Fukunaga; Atsushi Takeda (Annals of Clinical and Translational Neurology, 2022)
Abstract Background Increasing evidence suggests that alpha‐synuclein (αSyn) accumulation in cholinergic and adrenergic fibers in the skin is a useful biomarker to diagnose idiopathic Parkinson's disease (IPD). It has been widely reported that phosphorylated αSyn (p‐αSyn) deposits in autonomic fibers in IPD are a biomarker in the skin, but other tissue localizations have not been fully investigated. Objective It has been previously suggested that αSyn aggregates activate peripheral macrophages and that peripheral macrophages ingest pathological αsyn aggregates in aged rats or IPD patients. However, it remains to be elucidated whether peripheral macrophages in the skin of IPD patients accumulate αSyn. We evaluated whether (1) p‐αSyn deposits in dermal macrophages might represent a useful biomarker for IPD and (2) dermal macrophages play a role in the underlying pathogenesis of IPD. Methods We performed an immunohistological analysis of skin biopsy specimens from IPD patients and controls. Results We found that (1) p‐αSyn accumulation is present in dermal macrophages in skin biopsy specimens from patients with IPD, (2) not only dermal adrenergic fibers with p‐αSyn deposits but also dermal macrophages with p‐αSyn deposits are useful biomarkers for IPD patients and (3) the number of macrophages was significantly positively correlated with the number of macrophages with p‐αSyn deposits in the dermis of IPD patients. Interpretation Our results suggest that dermal macrophages, which are innate immune cells, play an important role in IPD patients and are a novel biomarker for IPD.